Exploring parental knowledge, care-seeking, and support strategies for neonatal illness: an integrative review of the African Great Lakes region - Sarah Farrell; Tracey A. Mills; Dame Tina Lavender (Global Health Action)
Background Sub-Saharan Africa shoulders much of the global burden of neonatal mortality. Quality postnatal care is often lacking due to availability, accessibility, mistrust of health systems, and socio-economic barriers, yet delays in care-seeking contribute to avoidable neonatal deaths. Research highlights the urgent need for improved health education about neonatal illness; however, contextual factors are rarely considered, and few interventions have been implemented. Objectives To critically examine the literature on parents’ knowledge of neonatal illness and care-seeking behaviour and evaluate interventions supporting parental understanding in sub-Saharan African Great Lakes countries. Methods Systematic searches were conducted in CINAHL, MEDLINE, Global Health, the Cochrane Library, and thesis repositories. Studies meeting inclusion criteria were critically analysed using Whittemore and Knafl’s framework, and quality was assessed with Hawker et al.’s tool, following PRISMA guidelines. Results Seventy studies (48 quantitative, 14 qualitative, eight mixed methods) were reviewed. The first theme, “poor knowledge of neonatal illness”, showed parents struggled to recognise illness, with knowledge affected by maternity and socio-economic factors. The second theme, “sub-optimal healthcare-seeking behaviour”, highlighted delayed care-seeking due to cultural, social, and economic factors. Finally, “strategies to support parents’ understanding” emphasised the roles of community workers, health education phone calls, SMS, and videos, and neonatal monitoring systems. Conclusions Parental knowledge of neonatal illness is generally low, and care-seeking is influenced by beliefs, trust in healthcare, and logistical challenges. While community health workers and multi-media interventions appear effective, health education efforts must address contextual barriers and beliefs to improve recognition and care-seeking for neonatal illness.